The role of the research phase in information seeking behaviour of Jewish studies scholars: a modification of Ellis's behavioural characteristics - Jenny Bronstein (Information Research: An International Electronic Journal)
Introduction. This study reports the application of Ellis's behavioural model to the information seeking behaviour of Jewish studies scholars. Method. A qualitative study in which twenty-five scholars from four universities in Israel were interviewed using a semi-structured interview guide in which participants were encouraged to talk about different aspects of their information seeking behaviour. Analysis. Data were analysed using the grounded theory approach. This method consists of identifying incidents, events and activities and coding them into their respective categories by constantly comparing them to the properties of the emerging category to develop and saturate the category. Results. Findings point to a strong relationship between the information activities used and the stage of the research or purpose of the search. Conclusion. The proposed innovation positions of each of Ellis's information activities within a time frame or relating them to a specific type of scholarly activity. The proposed revision gives a comprehensive view of the active stages of the information seeking process through the information activities used at each research phase.